Comparative income taxation a structural analysis - Ault, Hugh J. (Wolters Kluwer, 2020)
"In complex national income tax systems, structural and design variations from one country to another present major obstacles to the kind of comparative understanding that economic globalization requires. Hence the great significance of this book, now thoroughly updated to encompass the latest changes and trends. In it, leading authorities from eleven of the world's most important national taxation systems each contribute their particular expertise to a study of specific crucial problems of tax design. In addition to the nine countries covered in previous editions: Australia, Canada, France, Germany, Japan, the Netherlands, Sweden, the United Kingdom and the United States, China and India have now been added to provide the perspective of developing countries"--Provided by the publisher.